Preclinical optimization of a GPC2-targeting CAR T-cell therapy for neuroblastoma - Nan Li; Haiying Qin; Rosa Nguyen; Mitchell Ho; Ming Sun; Eytan Ruppin; Michael C Kelly; Yingying Cao; Reona Okada; Jeyshka M Reyes-González; Hannah G Stack; Charlie Seibert; et al. (Journal for ImmunoTherapy of Cancer)
Background Although most patients with newly diagnosed high-risk neuroblastoma (NB) achieve remission after initial therapy, more than 50% experience late relapses caused by minimal residual disease (MRD) and succumb to their cancer. Therapeutic strategies to target MRD may benefit these children. We developed a new chimeric antigen receptor (CAR) targeting glypican-2 (GPC2) and conducted iterative preclinical engineering of the CAR structure to maximize its anti-tumor efficacy before clinical translation.Methods We evaluated different GPC2-CAR constructs by measuring the CAR activity in vitro. NOD-SCID mice engrafted orthotopically with human NB cell lines or patient-derived xenografts and treated with human CAR T cells served as in vivo models. Mechanistic studies were performed using single-cell RNA-sequencing.Results Applying stringent in vitro assays and orthotopic in vivo NB models, we demonstrated that our single-chain variable fragment, CT3, integrated into a CAR vector with a CD28 hinge, CD28 transmembrane, and 4-1BB co-stimulatory domain (CT3.28H.BBζ) elicits the best preclinical anti-NB activity compared with other tested CAR constructs. This enhanced activity was associated with an enrichment of CD8+ effector T cells in the tumor-microenvironment and upregulation of several effector molecules such as GNLY, GZMB, ZNF683, and HMGN2. Finally, we also showed that the CT3.28H.BBζ CAR we developed was more potent than a recently clinically tested GD2-targeted CAR to control NB growth in vivo.Conclusion Given the robust preclinical activity of CT3.28H.BBζ, these results form a promising basis for further clinical testing in children with NB.